BackMatter (Copyright Transfer Agreement Form, Publication Ethics, Submission Information) - Editorial Team (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
Frontmatter J-Lalite: Journal of English Studies Volume 1, Issue 2 December 2020